ANALYSIS OF CERAMIC DISTRIBUTORS PT. SELAMET MITRA RAHARJA KOTA CIREBON - Taufik Ridwan; Diah Anariah (Syntax Corporation Indonesia, 2020)
The purpose of writing this journal is to identify the extent ofstudent enthusiasm in implementing campus programs, whichare internships in companies. The type of method used isqualitative so that the results obtained in the form of benefitsand application of knowledge gained while sitting on thelecture bench.Keywords: internships, benefits, application of knowledge